Murder one (New York Ballantine Books, 2001)
Tulsa defense attorney Ben Kincaid faces his own day in court after a major technical blunder on the part of overzealous cops frees Kincaid's client, stripper Keri Dalcanton, who had been on trial for the brutal murder of a veteran police detective.
Reprint. Originally published: 2001.
Keywords: Kincaid, Ben (Fictitious character) -- Fiction; Stripteasers -- Fiction; Tulsa (Okla.) -- Fiction; Detective and mystery stories; Legal stories